A study of anxiety experienced by EFL students in speaking performance - Nira Erdiana; Bukhari Daud; Diana Fauzia Sari; Shindy Khusuma Dwitami (Universitas Syiah Kuala, 2020)
Many EFL students show anxiety when speaking English in Indonesia. Therefore, the researchers were interested to conduct this study to find out the level of English-speaking anxiety experienced by those students. In this quantitative study, data were collected from 29 students through a questionnaire that was adopted from the Foreign Language Classroom Anxiety Scale (FLCAS) consisted of 10 items developed by Horwitz, et al. (1986). The data from the questionnaire were analyzed by using the FLCAS questionnaire scale. The results were described in percentages and are further elaborated in narration. The data revealed that 11 out of 29 students (38%) experienced low-level anxiety, 17 out of 29 students (59%) had anxiety at a moderate level, and one out of 29 students (3,4%) got high-level anxiety. It means that most students experienced a moderate level of speaking anxiety. In this case, those findings can be the inputs for every English teacher, especially for the English teachers in which this study was conducted, to be aware of the level of their students’ English-speaking anxiety. It is hoped that the findings of this research can give information and add knowledge to English teachers about EFL students’ level of anxiety so that they could find an appropriate strategy to reduce their students’ speaking anxiety.